Performance Modeling and Simulation for Wastewater Collection Networks - Ganjidoost, Amin; Knight, Mark A.; Unger, Andre J. A.; Haas, Carl T. (Frontiers in Water, 2022)
This study develops a framework for asset management strategy of wastewater collection networks comprised of three interconnected decision-making layers: 1) Visions & Values, 2) Function, and 3) Performance, which are set according to the established concepts of strategic targets, policy levers, sustainability and life cycle. The asset management strategy framework is implemented and validated through demonstration of functionality and value by using the wastewater collection networks of three utilities in Ontario, Canada, to drive management simulations. A borrowing management strategy is used to benchmark the utilities against each other in terms of infrastructure, sociopolitical, and financial performance over a 100-year benchmarking period. It is found that a borrowing management strategy can enable the utility to accelerate its capital works, reduces the volume of inflow and infiltration and its associated expenses and sustainably meets its strategic targets over the life cycle of the assets. The impact of maximum debt capacity on two infrastructure and financial benchmarking performance indicators are also investigated to explore the "optimal" combination of allowable fee hikes and preferred rehabilitation rates, using contour plots. Furthermore, a business case for asset management of wastewater collection networks using a borrowing management strategy is developed to explore the "optimal" combination of allowable fee-hike and rehabilitation rates, using a developed inflow and infiltration expenditures (I&IEx) saving ratio contour plots. The results indicate that a borrowing management strategy competes as long as the combinations of allowable fee-hike and preferred rehabilitation rates lead to a positive value of the I&IEx saving ratio.